Perceptions of fall prevention and engagement in social prescribing activities among older adults: A cross-sectional study in Portugal - Matos, C.; Baixinho, C. R.; Alarcão, V.; Henriques, M. A.; Ferreira, R. O.; Nascimento, T.; Arriaga, M.; Alves, T.; Nogueira, P.; Costa, A. (Healthcare, 2025)
Background: Falls are a major cause of injury, functional decline, and reduced quality of life among older adults, posing a significant public health challenge. Social prescribing is gaining relevance in gerontology, offering structured strategies to engage individuals in preventive activities, including fall prevention strategies, through engagement in community-based activities. Aim: To examine older adults’ perception of the relevance of personal protection and development activities (e.g., prevention against falling) and compare sociodemographic, behavioural, and engagement profiles between those who agree and those who disagree with its relevance. Methods: A cross-sectional study was conducted with 613 older adults aged 65–93 years. Data collection included sociodemographic, health-related, and behavioural/social engagement variables (including perceptions regarding the benefits of social prescribing and interest in community-based activities). For this analysis, participants were dichotomized based on their agreement with the relevance of personal protection and development activities (e.g., prevention against falling). Of the 569 participants included, 538 (94.5%) agreed with its relevance and 31 (5.5%) disagreed. Descriptive and exploratory analyses were conducted to compare the two groups across variables. Multivariate logistic regression analyses were conducted to explore independent predictors of agreement across sociodemographic, behavioural, social prescribing, and health-related variables. Results: Significant differences were observed between the groups in awareness of active ageing (p = 0.018), volunteering (p < 0.001), participation in social and community activities (p < 0.001), and hobbies like gardening, fishing, or cooking (p = 0.002). Those who agreed with the importance of personal protection and development activities were significantly more likely to value a range of initiatives, including social activities in recreational organizations, physical activity in the community (e.g., hiking), artistic and creative activities (e.g., visual arts, music), technical or technological activities (e.g., do-it-yourself, computers), and cultural enrichment activities (e.g., visiting museums), (p < 0.001). Multivariate analyses showed no effects of sociodemographic or health-related factors, whereas behavioural and engagement-related variables—including volunteering, hobbies, and several social prescribing activities—significantly predicted agreement with the relevance of personal protection and development activities. Discussion: The findings suggest that older adults who perceive fall prevention as relevant are more actively engaged in diverse health-promoting activities, including volunteering, hobbies, and community-based programmes. This pattern may reflect higher health literacy, stronger social networks, and proactive attitudes towards ageing. Conclusions: Perceptions of fall prevention are closely linked to broader patterns of engagement in health-promoting activities among older adults. Recognizing and addressing differences in how these activities are valued can inform more inclusive and targeted gerontological interventions.